A permanent magnet motor with rotor flux barriers - Misron, Norhisam; Raja Nor Firdaus (2013)
A single stator permanent magnet motor that has a series magnetic circuit topology using a flux barrier has been disclosed. The single stator permanent magnet motor using the flux barrier eliminates the unused flux by channeling it to the air gap between a permanent magnet and a stator of the motor; thereby the unused flux contributes in the torque production. Thus, there is an increase in the torque being produced compared to conventional single stator permanent magnet motor with parallel magnetic circuit that has the same motor volume. Furthermore, the single stator permanent magnet motor can be operated as a DC brushless motor, a stepper motor or a synchronous motor depending upon the type of motor driver. The single stator permanent magnet motor due to its design and high torque production capability facilitates in development of portable domestic appliances that have certain limitations including space, weight and electrical power accessibility.